2014
DOI: 10.1063/1.4893346
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation on topological properties of layered GaS and GaSe under strain

Abstract: The topological properties of layered β-GaS and ε-GaSe under strain are systematically investigated by ab initio calculations with the electronic exchange-correlation interactions treated beyond the generalized gradient approximation (GGA). Based on the GW method and the Tran-Blaha modified Becke-Johnson potential approach, we find that while ε-GaSe can be strain-engineered to become a topological insulator, β-GaS remains a trivial one even under strong strain, which is different from the prediction based on G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Out of many earlier calculations, we single out that of An et al. () done on ϵ‐GaSe (also studied by us but omitted in the present report for brevity), using notably WIEN2k, PBEsol, and mBJ, in a row of other XC flavours. An important message from this work concerning our present one is that the spin‐orbit interaction (neglected in our case), apparently, has no noticeable effect onto the lattice parameters and the band gap values of GaSe.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Out of many earlier calculations, we single out that of An et al. () done on ϵ‐GaSe (also studied by us but omitted in the present report for brevity), using notably WIEN2k, PBEsol, and mBJ, in a row of other XC flavours. An important message from this work concerning our present one is that the spin‐orbit interaction (neglected in our case), apparently, has no noticeable effect onto the lattice parameters and the band gap values of GaSe.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…It demonstrates interesting electrical and optical properties, such as a high on/off ratio [ 7 , 14 ], large anisotropic Hall mobility [ 7 , 15 ], good gas sensibility [ 16 ], and strong second-harmonic generation [ 17 ]. More recently, it has also been shown that the electronic band structures and PL intensity of layered GaSe can be effectively tuned via the elastic strain engineering [ 18 , 19 , 20 ]. These flexible electrical and optical properties make it an appealing candidate for mechanically compliant optoelectronics with applications in piezo-phototronics, optoelectronics, wearable devices and human–machine interfaces [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results calculated from PBE and HSE functionals are given, and results with and without spin-orbit coupling are listed. The effects of AA' versus AA stacking order of GaS and AA' versus ǫ stacking order of GaSe 72,73 are also compared.…”
Section: Numerical Resultsmentioning
confidence: 99%